Moral Deference, Moral Assertion, and Pragmatics - Lewis, Max (Ethical theory and moral practice, 2020)
In this paper, I offer a novel defense of moderate pessimism about moral deference, i.e., the view that we have pro tanto reason to avoid moral deference. I argue that moral deference fails to give us the epistemic credentials to satisfy plausible norms of moral assertion. I then argue that moral assertions made solely on the basis of deferential moral beliefs violate a plausible epistemic and moral norm against withholding information that one knows, has evidence, or ought to believe will importantly affect another person's deliberation. Finally, I argue that not only does moral deference fail to put the audience in a good epistemic position it also puts the audience in a bad epistemic and moral position. First, there is a tight connection between outright believing something and being disposed to assert it and so deferential moral beliefs often motivate people to assert something that they don't have the epistemic credentials to properly assertion. Second, there will often be moral reasons to make assertions—even based on deferential moral beliefs. These assertions, while all-things-considered permissible, will be epistemic impermissible and involve violating a moral norm.